“Crooked Magnetism” of Maxwell (without real magnetic charges) as the age-old imprecation of Physical Science - Sizov, Robert A. (European Journal of Applied Sciences, 2021)
Experimental and theoretical studies of the author (period: 1968 - present) have shown that magnetic fundamental particles (magnetic charges) are real structural components of atoms and substance. It is the magnetic charges, and not the electrons moving are the direct sources of all magnetic fields and magnetic manifestations in nature. Magnetic charges together with electric charges make up the shells of atoms which in reality are electromagnetic, and not electronic. It is the shells of atoms and nucleons that are the sources of the gravitational field, which is a vortex electromagnetic field. The main reason for ignoring magnetic charges, as well as true antielectronsа in physical science are the harsh conditions for their confinement in the structures of substance which is cardinally different from confinement of electrons. In addition, a very negative role in the “fate” of the noted problematic particles was played by Maxwell's vicious concept of electric magnetism, in which the great physicist, back in 1873, based on his superficial impressions of the famous Oersted Experiment declared moving electrons by the direct sources of the magnetic field. Paradoxically, the world physical community has accepted Maxwell's erroneous concept as the absolute truth and, for almost 150 years, his vicious electric magnetism largely determines the "development" of world fundamental physics. The article shows how the introduction of these problematic particles into basic physics radically changes the representation of most physical effects and manifestations. So, for example, the gravitational field in physics with magnetic charges is just the vortex electromagnetic field that has nothing to do with the ritual curvature of 4-dimensional space-time. To obtain a gravitational field and use it in practice, it is necessary to legalize magnetic charges and learn how to work with them in superconductivity conditions.